Chronic granulomatous disease: is it always associated with infections? - BARIŞ, SAFA; AKALIN, FİGEN (My University, 2012)
Chronic granulomatous disease (CGD) is a rare disease of the phagocytic system characterized by mutation in nicotinamide adenine dinucleotide phosphate oxidase enzyme system. The heredity of disease is heterogeneous and X-linked genotype accounts for the most common type (65-70%). In patients with CGD reduction of reactive oxygen intermediates in phagocytes have result in susceptibility to catalase positive bacterial and fungal infections and abscess formation. Pericardial effusion and CGD coexistence is very rare condition and may occur during invasive fungal infections or secondary to enhanced inflammation. Twenty-month-old boy presented with fever and palpitation. On physical examination tachycardia and pericardial effusion was revealed (width: 11 mm) and his history was notable for perianal abscess in newborn period. Therefore, CGD was included in the differential diagnosis which was confirmed by nitroblue tetrazolium and dihidrorhodamin test. Despite negativity of microbiological culture for bacterial and fungal microorganisms the patient was placed on broad-spectrum antibacterial, antifungal and anti-inflammatory treatment. His condition improved without any complication. In this report, we emphasize that in patient with CGD pericardial effusion may be occurred secondary to increased inflammation without any microbial causes and can be resolved during clinical follow-up.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; ALERJİ; Klinik Tıp; Klinik Tıp (MED); ALLERGY; CLINICAL MEDICINE; Clinical Medicine (MED); İmmünoloji ve Alerji; Immunology and Allergy; Chronic granulomatous disease; pericardial effusion; inflammation